Copolymer latex for adhesive and adhesive composition
By using the emulsion polymerization of specific monomer compositions, the problem of difficulty in taking into account both adhesive strength and softness in the prior art is solved, and the copolymerization of high adhesive strength and softness is achieved latex, suitable for bonding between rubber and fiber materials.
Patent Information
- Application Number
- CN202080048544.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-02
- Filing Date
- 2020-06-15
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-06-15
AI Technical Summary
The existing copolymer latex for adhesives is difficult to take into account both the adhesive strength and the softness of the tire cord.
Copolymer latex (A) and (B) containing specific monomer compositions (a) and (b) are used, wherein the monomer composition (a) contains 35-75% butadiene monomer, 10-30% vinylpyridine monomer and 10-55% styrene monomer, monomer composition (b) contains 3-30% butadiene monomer and 50-85% styrene monomer, latex (B) The solid component ratio is between 5-15%, and the average particle size of latex particles is above 150 nm.
It achieves improving the flexibility of the tire cord without reducing the adhesive force, and is suitable for bonding rubber and fiber materials.
Smart Images

Figure BDA0003450120340000111 
Figure BDA0003450120340000131 
Figure BDA0003450120340000141
Abstract
Description
Technical Field
[0001] The present invention relates to a copolymer latex for adhesives, and more particularly to a copolymer latex for adhesives for bonding rubber and fibers, and an adhesive composition containing the copolymer latex for adhesives. Background Art
[0002] Conventionally, there is known a copolymer latex for an adhesive agent comprising 50 to 90% by mass of a copolymer latex (A) and 10 to 50% by mass of a copolymer latex (B).
[0003] The copolymer latex (A) is obtained by emulsion polymerization of a monomer composition (a) containing 35 to 75% by mass of a butadiene monomer, 10 to 30% by mass of a vinyl pyridine monomer, and 10 to 55% by mass of a styrene monomer. The copolymer latex (B) is obtained by emulsion polymerization of a monomer composition (b) containing 3 to 25% by mass of a butadiene monomer, 0 to 5% by mass of a vinyl pyridine monomer, 55 to 97% by mass of a styrene monomer, 0 to 10% by mass of an ethylenically unsaturated carboxylic acid, and 0 to 20% by mass of other copolymerizable monomers (for example, refer to Patent Document 1 below).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2011 / 102003 Summary of the invention
[0007] Technical problem to be solved by the invention
[0008] However, it is difficult for the adhesive copolymer latex described in Patent Document 1 to achieve both adhesive strength and flexibility of the tire cord.
[0009] Therefore, an object of the present invention is to provide a copolymer latex for an adhesive and an adhesive composition which are intended to achieve both adhesive strength and flexibility of a tire cord.
[0010] Technical solutions adopted to solve technical problems
[0011] The present invention [1] comprises a copolymer latex for an adhesive, comprising a copolymer latex (A) which is an emulsion polymer of a monomer composition (a) containing 35% by mass to 75% by mass of a butadiene monomer, 10% by mass to 30% by mass of a vinyl pyridine monomer, and 10% by mass to 55% by mass of a styrene monomer, and a copolymer latex (B) which is an emulsion polymer of a monomer composition (b) containing 3% by mass to 30% by mass of the butadiene monomer, wherein the ratio of the solid content of the copolymer latex (B) to the total amount of the solid content of the copolymer latex (A) and the solid content of the copolymer latex (B) is 5% by mass to 15% by mass, and the number-based average particle size of the latex particles in the copolymer latex (B) is 150 nm or more.
[0012] The present invention [2] comprises the adhesive copolymer latex of the above [1], wherein the monomer composition (b) further contains 50% by mass to 85% by mass of the styrene monomer and 30% by mass to 30% by mass of the vinylpyridine monomer.
[0013] The present invention [3] comprises the adhesive copolymer latex of the above-mentioned [1] or [2], wherein the above-mentioned monomer composition (a) contains 50% by mass or more of the above-mentioned butadiene monomer.
[0014] The present invention [4] comprises the copolymer latex for adhesives according to any one of [1] to [3], wherein the ratio of the copolymer latex (B) to the total amount of the copolymer latex (A) and the copolymer latex (B) is 10% by mass or more.
[0015] The present invention [5] includes an adhesive composition comprising a copolymer latex (A) which is an emulsion polymer of a monomer composition (a) containing 35% by mass or more and 75% by mass or less of a butadiene monomer, 10% by mass or more and 30% by mass or less of a vinyl pyridine monomer, and 10% by mass or more and 55% by mass or less of a styrene monomer, a copolymer latex (B) which is an emulsion polymer of a monomer composition (b) containing 3% by mass or more and 30% by mass or less of the butadiene monomer, and a resorcinol-formalin resin, wherein the ratio of the solid content of the copolymer latex (B) to the total amount of the solid content of the copolymer latex (A) and the solid content of the copolymer latex (B) is 5% by mass or more and 15% by mass or less, and the number-based average particle size of the latex particles in the copolymer latex (B) is 150 nm or more.
[0016] Effects of the Invention
[0017] By using the adhesive copolymer latex and the adhesive composition of the present invention, it is possible to achieve both adhesive strength and flexibility of the tire cord. DETAILED DESCRIPTION
[0018] 1. Copolymer latex for adhesive
[0019] The copolymer latex for adhesives contains the copolymer latex (A) and the copolymer latex (B). Preferably, the copolymer latex for adhesives is composed of the copolymer latex (A) and the copolymer latex (B).
[0020] (1) Copolymer latex (A)
[0021] The copolymer latex (A) is an emulsion polymer of a monomer composition (a). The monomer composition (a) contains a butadiene monomer, a vinyl pyridine monomer, and a styrene monomer. In other words, the latex particles in the copolymer latex (A) have a structural unit derived from a butadiene monomer, a structural unit derived from a vinyl pyridine monomer, and a structural unit derived from a styrene monomer.
[0022] Examples of the butadiene monomer include 1,3-butadiene, 2-methyl-1,3-butadiene, and 2,3-dimethyl-1,3-butadiene. The butadiene monomer is preferably 1,3-butadiene. The monomer composition (a) may contain one or more butadiene monomers.
[0023] Examples of the vinyl pyridine monomer include 2-vinyl pyridine, 3-vinyl pyridine, 4-vinyl pyridine, and 2-methyl-5-vinyl pyridine. The vinyl pyridine monomer is preferably 2-vinyl pyridine. The monomer composition (a) may contain one vinyl pyridine monomer. The monomer composition (a) may also contain a plurality of vinyl pyridine monomers.
[0024] Examples of the styrene monomer include styrene, α-methylstyrene, and monochlorostyrene. The styrene monomer is preferably styrene. The monomer composition (a) may contain one styrene monomer. The monomer composition (a) may contain a plurality of styrene monomers.
[0025] The monomer composition (a) contains 35% by mass or more, preferably 45% by mass or more, more preferably 50% by mass or more, and 75% by mass or less, preferably 70% by mass or less of a butadiene monomer. In other words, the latex particles in the copolymer latex (A) contain 35% by mass or more, preferably 45% by mass or more, more preferably 50% by mass or more, and 75% by mass or less, preferably 70% by mass or less of a structural unit derived from a butadiene monomer.
[0026] When the ratio of the butadiene monomer in the monomer composition (a) is at least 35 mass % and no more than 75 mass %, both the adhesive strength and the flexibility of the tire cord can be achieved.
[0027] Here, the adhesive strength refers to the adhesive strength between the tire cord treated with the adhesive composition containing the adhesive copolymer latex and the rubber. The adhesive composition will be described later. The adhesive strength is the initial adhesive strength and the heat-resistant adhesive strength. The initial adhesive strength and the heat-resistant adhesive strength are measured by ASTM D2138-67 (H PULL Test).
[0028] The flexibility of the tire cord refers to the flexibility of the tire cord treated with the adhesive composition containing the adhesive copolymer latex.
[0029] If the ratio of the butadiene monomer in the monomer composition (a) is between 50% by mass and 75% by mass, the flexibility of the tire cord can be improved. In addition, if the ratio of the butadiene monomer in the monomer composition (a) is less than 35% by mass, the initial adhesion decreases and the flexibility of the tire cord decreases. If the ratio of the butadiene monomer in the monomer composition (a) exceeds 75% by mass, the heat-resistant adhesion decreases.
[0030] Furthermore, the monomer composition (a) contains 10% by mass or more, preferably 15% by mass or more and 30% by mass or less, preferably 25% by mass or less of a vinyl pyridine monomer. In other words, the latex particles in the copolymer latex (A) contain 10% by mass or more, preferably 15% by mass or more and 30% by mass or less, preferably 25% by mass or less of a structural unit derived from a vinyl pyridine monomer.
[0031] If the monomer composition (a) contains 10% to 30% by mass of vinyl pyridine monomer, both the adhesive strength and the softness of the tire cord can be taken into account. On the other hand, if the proportion of the vinyl pyridine monomer in the monomer composition (a) is less than 10% by mass, the initial adhesive strength decreases. If the proportion of the vinyl pyridine monomer in the monomer composition (a) exceeds 30% by mass, the initial adhesive strength and the heat-resistant adhesive strength decrease, and the softness of the tire cord decreases.
[0032] In addition, the monomer composition (a) contains 10% by mass or more and 55% by mass or less, preferably 50% by mass or less, and more preferably 30% by mass or less of a styrene monomer. In other words, the latex particles in the copolymer latex (A) contain 10% by mass or more and 55% by mass or less, preferably 50% by mass or less, and more preferably 30% by mass or less of a structural unit derived from a styrene monomer.
[0033] If the proportion of the styrene monomer in the monomer composition (a) is between 10% by mass and 55% by mass, both the adhesive strength and the softness of the tire cord can be taken into account. Furthermore, if the proportion of the styrene monomer in the monomer composition (a) is between 10% by mass and 30% by mass, the softness of the tire cord can be improved. On the other hand, if the proportion of the styrene monomer in the monomer composition (a) is less than 10% by mass, the heat-resistant adhesive strength decreases.
[0034] The monomer composition (a) may also contain other monomers copolymerizable with the butadiene monomer, the vinylpyridine monomer, and the styrene monomer.
[0035] As other monomers, there may be mentioned cyanide monomers such as acrylonitrile and methacrylonitrile, ethylenic unsaturated carboxylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid, ethylenic unsaturated carboxylic acid alkyl ester monomers such as methyl methacrylate, ethyl acrylate, butyl acrylate, ethylenic unsaturated carboxylic acid hydroxyalkyl ester monomers such as β-hydroxyethyl acrylate and β-hydroxyethyl methacrylate, amide monomers such as acrylamide and methacrylamide, etc. The monomer composition (a) may contain one other monomer. The monomer composition (a) may also contain a plurality of other monomers.
[0036] The monomer composition (a) is preferably composed of butadiene monomers, vinylpyridine monomers and styrene monomers.
[0037] The number-based average particle size of the latex particles in the copolymer latex (A) is, for example, 50 nm or more, preferably 90 nm or more, and for example, 200 nm or less, preferably 150 nm or less.
[0038] The average particle size is determined by staining the copolymer latex with osmium tetroxide, taking a transmission electron microscope photograph, measuring the diameters of 1,000 particles using an image analysis processing device (device name: IP-1000PC manufactured by Asahi Kasei Corporation), and averaging the diameters.
[0039] (2) Copolymer latex (B)
[0040] Copolymer latex (B) is an emulsion polymer of monomer composition (b). Monomer composition (b) contains butadiene monomer, styrene monomer, and vinyl pyridine monomer as required. In other words, the latex particles in copolymer latex (B) have structural units derived from butadiene monomer, structural units derived from styrene monomer, and structural units derived from vinyl pyridine monomer as required. In addition, monomer composition (b) may also contain other monomers that can be copolymerized with butadiene monomer, vinyl pyridine monomer and styrene monomer. Preferably, monomer composition (b) is composed of butadiene monomer, styrene monomer, and vinyl pyridine monomer.
[0041] As the butadiene monomer, the styrene monomer, the vinylpyridine monomer and other monomers, the same monomers as exemplified for the copolymer latex (A) may be mentioned respectively.
[0042] The monomer composition (b) contains 3% by mass or more, preferably 10% by mass or more, more preferably 15% by mass or more and 30% by mass or less of a butadiene monomer. In other words, the latex particles of the copolymer latex (B) contain 3% by mass or more, preferably 10% by mass or more, more preferably 15% by mass or more and 30% by mass or less of a structural unit derived from a butadiene monomer.
[0043] If the ratio of the butadiene monomer in the monomer composition (b) is between 3% by mass and 30% by mass, both the adhesive strength and the softness of the tire cord can be achieved. On the other hand, if the ratio of the butadiene monomer in the monomer composition (b) is less than 3% by mass, the initial adhesive strength decreases. If the ratio of the butadiene monomer in the monomer composition (b) exceeds 30% by mass, the heat-resistant adhesive strength decreases.
[0044] In addition, the monomer composition (b) contains, for example, 50% by mass or more, preferably 55% by mass or more, and for example, 85% by mass or less, preferably 82% by mass or less of a styrene monomer. In other words, the latex particles of the copolymer latex (B) contain, for example, 50% by mass or more, preferably 55% by mass or more, and for example, 85% by mass or less, preferably 82% by mass or less of a structural unit derived from a styrene monomer.
[0045] When the ratio of the styrene monomer in the monomer composition (b) is 50 mass % or more and 85 mass % or less (ie, 50 to 85 mass %), both the adhesive strength and the flexibility of the tire cord can be achieved.
[0046] When the monomer composition (b) contains a vinylpyridine monomer, the vinylpyridine monomer is contained in an amount of, for example, 30% by mass or less, preferably 15% by mass or less and, for example, 3% by mass or more. In other words, the latex particles of the copolymer latex (B) contain, for example, 30% by mass or less, preferably 15% by mass or less and, for example, 3% by mass or more of a structural unit derived from the vinylpyridine monomer.
[0047] When the proportion of the vinylpyridine monomer in the monomer composition (b) is at most 30 mass %, both the adhesive strength and the flexibility of the tire cord can be achieved.
[0048] The average particle size of the latex particles in the copolymer latex (B) based on the number of particles is different from the average particle size of the latex particles in the copolymer latex (A). The average particle size of the latex particles in the copolymer latex (B) based on the number of particles is larger than the average particle size of the latex particles in the copolymer latex (A). The average particle size of the latex particles in the copolymer latex (B) based on the number of particles is 150 nm or more, for example, 250 nm or less, preferably 200 nm or less, and more preferably 180 nm or less.
[0049] If the average particle size of the latex particles in the copolymer latex (B) is 150 nm or more, both the adhesive strength and the softness of the tire cord can be achieved. On the other hand, if the average particle size of the latex particles in the copolymer latex (B) is less than 150 nm, the adhesive strength (initial adhesive strength and heat-resistant adhesive strength) decreases.
[0050] (3) Blending ratio of copolymer latex (A) and copolymer latex (B)
[0051] In the adhesive copolymer latex, the ratio of the solid content of the copolymer latex (A) to the total solid content of the copolymer latex (A) and the solid content of the copolymer latex (B) is 85% by mass or more, preferably 88% by mass or more and 95% by mass or less, preferably 92% by mass or less.
[0052] In the adhesive copolymer latex, the ratio of the solid content of the copolymer latex (B) to the total solid content of the copolymer latex (A) and the solid content of the copolymer latex (B) is 5 mass % or more, preferably 8 mass % or more and 15 mass % or less, preferably 12 mass % or less.
[0053] If the ratio of the solid content of the copolymer latex (B) relative to the total amount of the solid content of the copolymer latex (A) and the solid content of the copolymer latex (B) is 5% by mass or more and 15% by mass or less, both the adhesive force and the softness of the tire cord can be taken into account. Furthermore, if the ratio of the solid content of the copolymer latex (B) relative to the total amount of the solid content of the copolymer latex (A) and the solid content of the copolymer latex (B) is 10% by mass or more and 15% by mass or less, the softness of the tire cord can be improved. On the other hand, if the ratio of the solid content of the copolymer latex (B) relative to the total amount of the solid content of the copolymer latex (A) and the solid content of the copolymer latex (B) is less than 5% by mass, the heat-resistant adhesive force decreases. If the ratio of the solid content of the copolymer latex (B) relative to the total amount of the solid content of the copolymer latex (A) and the solid content of the copolymer latex (B) exceeds 15% by mass, the softness of the tire cord decreases.
[0054] 2. Production of copolymer latex for adhesives
[0055] (1) Production of copolymer latex
[0056] In order to produce the copolymer latex for adhesives, first, the copolymer latex (A) and the copolymer latex (B) are produced.
[0057] To obtain the copolymer latex (A), the monomer composition (a) is subjected to emulsion polymerization. To obtain the copolymer latex (B), the monomer composition (b) is subjected to emulsion polymerization.
[0058] In order to emulsion polymerize the monomer composition (a) or the monomer composition (b), for example, the monomer composition (a) or the monomer composition (b), water, and an emulsifier used as required are mixed to emulsify the monomer composition (a) or the monomer composition (b).
[0059] As the emulsifier, nonionic surfactants such as polyethylene glycol alkyl esters, alkylphenyl ethers, and alkyl ethers may be mentioned, and anionic surfactants such as rosin salts, fatty acid salts, higher alcohol sulfates, alkylbenzene sulfonates, alkyl diphenyl ether sulfonates, aliphatic sulfonates, aliphatic carboxylates, sulfates of nonionic surfactants, and formalin condensates of naphthalene sulfonates may be mentioned. Preferably, anionic surfactants may be mentioned, and more preferably, alkylbenzene sulfonates, rosin salts, and formalin condensates of naphthalene sulfonates may be mentioned. The emulsifier may be one or more.
[0060] The emulsifier may be added to the polymerization system by any method of all-at-once addition, continuous addition or batch addition. In consideration of the stability during polymerization, etc., the emulsifier may be added not only at the initial stage of polymerization but also during or after the completion of polymerization.
[0061] Next, a polymerization initiator is added to the emulsion of the monomer composition (a) or the monomer composition (b).
[0062] The polymerization initiator is a free radical polymerization initiator, and examples thereof include water-soluble polymerization initiators such as potassium persulfate, sodium persulfate, and ammonium persulfate, and oil-soluble polymerization initiators such as cumene hydroperoxide, benzoyl peroxide, tert-butyl hydroperoxide, acetyl peroxide, diisopropylbenzene hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide. As the water-soluble polymerization initiator, potassium persulfate, sodium persulfate, and ammonium persulfate are preferred, and as the oil-soluble polymerization initiator, cumene hydroperoxide is preferred.
[0063] Furthermore, in the emulsion polymerization of the monomer composition (a) or the monomer composition (b), a reducing agent, a chain transfer agent, a hydrocarbon solvent, or other additives may be added as necessary.
[0064] As the reducing agent, for example, sulfites, bisulfites, pyrosulfites, dithionites, dithionites, thiosulfates, formaldehyde sulfonates, benzaldehyde sulfonates, carboxylic acids such as L-ascorbic acid, isoascorbic acid, tartaric acid, citric acid and salts thereof, reducing sugars such as dextrose and sucrose, amines such as dimethylaniline and triethanolamine, etc. Preferably, carboxylic acids and salts thereof are mentioned, and more preferably, L-ascorbic acid and isoascorbic acid are mentioned.
[0065] Examples of the chain transfer agent include alkyl mercaptans such as n-hexyl mercaptan, n-octyl mercaptan, tert-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan and n-octadecyl mercaptan; xanthate compounds such as dimethyl xanthate dithioate and diisopropyl xanthate dithioate; thiuram compounds such as tetramethyl thiuram dithioate, tetraethyl thiuram dithioate and tetramethyl thiuram monothioate; phenol compounds such as 2,6-di-tert-butyl-4-methylphenol and styrenated phenol; Allyl compounds such as allyl alcohol, halogenated hydrocarbon compounds such as dichloromethane, dibromomethane, and carbon tetrabromide, vinyl ethers such as α-benzyloxystyrene, α-benzyloxyacrylonitrile, and α-benzyloxyacrylamide, triphenylethane, pentaphenylethane, acrolein, methacrolein, thioglycolic acid, thiomalic acid, 2-ethylhexyl thioglycolate, and α-methylstyrene dimer, etc., preferably, alkyl mercaptan, more preferably, n-octyl mercaptan and tert-dodecyl mercaptan. The chain transfer agent may be one or more.
[0066] The chain transfer agent is added in a ratio of, for example, 10 parts by mass or less, preferably 7 parts by mass or less and, for example, 0.05 parts by mass or more, based on 100 parts by mass of the monomer composition (a).
[0067] Examples of hydrocarbon solvents include saturated hydrocarbons such as pentane, hexane, heptane, octane, cyclohexane, and cycloheptane, and unsaturated hydrocarbons such as pentene, hexene, heptene, cyclopentene, cyclohexene, cycloheptene, 4-methylcyclohexene, and 1-methylcyclohexene. Preferably, cyclohexene is used. Cyclohexene is easy to recover and reuse by steam distillation after the polymerization at a low boiling point is completed, and is suitable from the viewpoint of environmental burden.
[0068] Examples of other additives include electrolytes such as sodium hydroxide, sodium carbonate, potassium carbonate and sodium bicarbonate, polymerization inhibitors such as hydroquinone, polymerization accelerators such as chelating agents, and the like.
[0069] In the production of copolymer latex (A) or copolymer latex (B), there is no limitation on the polymerization method, and batch polymerization, semi-batch polymerization, seed polymerization, etc. can be applied. In addition, there is no limitation on the method for adding the various components, and a one-time addition method, a batch addition method, a continuous addition method, an automatic feeding method, etc. can be adopted.
[0070] (2) Preparation of copolymer latex for adhesive
[0071] The copolymer latex for adhesives can be prepared by mixing the copolymer latex (A) and the copolymer latex (B) in the above ratio. Alternatively, the copolymer latex for adhesives can be prepared by diluting the mixture of the copolymer latex (A) and the copolymer latex (B) with water.
[0072] 3. Adhesive composition
[0073] The adhesive composition is blended with an adhesive copolymer latex. The adhesive composition is preferably used for bonding rubber and rubber reinforcing fibers.
[0074] The rubber is not particularly limited, and examples thereof include natural rubber, SBR, NBR, chloroprene rubber, polybutadiene rubber, polyisoprene rubber, and various modified rubbers of these rubbers. In addition, known additives such as fillers, softeners, vulcanizers, and vulcanization accelerators may be blended into the rubber.
[0075] Examples of the rubber reinforcing fibers include nylon fibers, polyester fibers, and aramid fibers. The form of these fibers is not particularly limited, and examples thereof include cords, cables, fabrics, canvas, and short fibers.
[0076] The adhesive composition contains an adhesive copolymer latex and a resorcinol-formalin resin. In other words, the adhesive composition contains a copolymer latex (A), a copolymer latex (B), and a resorcinol-formalin resin. The adhesive composition is prepared by mixing an adhesive copolymer latex and a resorcinol-formalin resin. In addition, the adhesive composition can also be prepared by mixing a copolymer latex (A), a copolymer latex (B), and a resorcinol-formalin resin.
[0077] The ratio of the resorcinol-formalin resin in the adhesive composition is, in terms of solid content, for example, 5 parts by mass or more and 100 parts by mass or less, preferably 90 parts by mass or less, based on 100 parts by mass of the adhesive copolymer latex.
[0078] In addition, the adhesive composition may also contain modified resorcinol-formalin resins such as isocyanate, blocked isocyanate, ethylene urea, 2,6-bis(2,4-dihydroxyphenylmethyl)-4-chlorophenol, a mixture of sulfur monochloride and a condensate of resorcinol and a resorcinol-formalin condensate, polyepoxides, modified polyvinyl chloride, carbon black and other bonding aids, fillers, crosslinking agents, vulcanizers, vulcanization accelerators, etc. as needed.
[0079] Then, when bonding the rubber and the rubber reinforcing fiber, first, the adhesive composition is used to treat the rubber reinforcing fiber.
[0080] In detail, the adhesive composition, for example, is used to immerse the rubber reinforcing fiber in the adhesive composition by a dip coater or the like. Next, the rubber reinforcing fiber impregnated with the adhesive composition is dried at, for example, 100° C. or more, preferably 110° C. or more, and at, for example, 150° C. or less, preferably 130° C. or less, for example, for 80 seconds or more, preferably 100 seconds or more, and for example, 200 seconds or less, preferably 150 seconds or less. Thereafter, the dried rubber reinforcing fiber is heated (sintered) at, for example, 180° C. or more, preferably 200° C. or more, and for example, 300° C. or less, preferably 260° C. or less, for example, for 30 seconds or more, preferably 50 seconds or more, and for example, 100 seconds or less, preferably 80 seconds or less. Thus, the treatment of the adhesive composition for the rubber reinforcing fiber is terminated.
[0081] After the above treatment, the rubber reinforcing fibers treated with the adhesive composition are brought into contact with the rubber, and the rubber and the rubber reinforcing fibers are heated and pressurized to bond the rubber and the rubber reinforcing fibers.
[0082] 4. Effect
[0083] The above-mentioned copolymer latex for adhesive and adhesive composition contain copolymer latex (A) and copolymer latex (B). Copolymer latex (A) is an emulsion polymer of a monomer composition (a) containing 35% by mass or more and 75% by mass or less of butadiene monomer, 10% by mass or more and 30% by mass or less of vinyl pyridine monomer, and 10% by mass or more and 55% by mass or less of styrene monomer. Copolymer latex (B) is an emulsion polymer of a monomer composition (b) containing 3% by mass or more and 30% by mass or less of butadiene monomer. The ratio of the solid content of copolymer latex (B) to the total amount of the solid content of copolymer latex (A) and the solid content of copolymer latex (B) is 5% by mass or more and 15% by mass or less, and the number-based average particle size of copolymer latex (B) is 150nm or more.
[0084] Thereby, both the adhesive strength and the softness of the tire cord can be achieved.
[0085] Example
[0086] Next, the present invention will be described based on examples and comparative examples, but the present invention is not limited to the following examples. In addition, the specific numerical values of the blending ratio or content ratio used in the following description can be replaced by the upper limit or lower limit of the blending ratio or content ratio corresponding to the above-mentioned specific embodiment.
[0087] 1. Production of copolymer latex (A)
[0088] (1) Synthesis Examples 1, 2 and Comparative Synthesis Examples 1 to 3
[0089] 130 parts by mass of water were placed in an autoclave equipped with a stirrer, and 1 part by mass of a formalin condensate of sodium naphthalenesulfonate (emulsifier), 0.5 parts by mass of sodium hydroxide (electrolyte), and 4 parts by mass of potassium rosinate (emulsifier) were dissolved.
[0090] Next, the monomer composition (a) shown in Table 1 and 0.55 parts by mass of tert-dodecyl mercaptan (chain transfer agent) were added and emulsified.
[0091] Thereafter, 0.5 parts by mass of potassium persulfate (polymerization initiator) was added to the emulsion, and the internal temperature was maintained at 50° C. to polymerize the monomer composition (a).
[0092] When the polymerization conversion rate reached 93%, 0.1 parts by mass of hydroquinone (polymerization inhibitor) was added to stop the polymerization, and then unreacted monomers were removed by distillation under reduced pressure to obtain copolymer latexes (A) of Synthesis Examples 1 and 2 and Comparative Synthesis Examples 1 to 3.
[0093] Table 1 shows the average particle size of the latex particles in the copolymer latex (A).
[0094] [Table 1]
[0095] Table 1
[0096]
[0097] (2) Synthesis example 3
[0098] 135 parts by mass of water were placed in an autoclave equipped with a stirrer, and 1 part by mass of a formalin condensate of sodium naphthalenesulfonate, 0.5 parts by mass of sodium hydroxide, and 5.0 parts by mass of potassium rosinate (emulsifier) were dissolved.
[0099] Next, the first-stage monomer composition (a) shown in Table 1 and 0.3 parts by mass of tert-dodecyl mercaptan were added and emulsified.
[0100] Thereafter, 0.5 parts by mass of potassium persulfate was added to the emulsion, and the internal temperature was maintained at 55° C. to polymerize the first-stage monomer composition (a).
[0101] When the polymerization conversion rate of the first-stage monomer composition (a) reached 82%, the second-stage monomer composition (a) shown in Table 1 and 0.25 parts by mass of tert-dodecyl mercaptan were continuously added to continue polymerization.
[0102] When the polymerization conversion rate reached 93%, 0.1 parts by mass of hydroquinone (polymerization inhibitor) was added to stop the polymerization, and then unreacted monomers were removed by distillation under reduced pressure to obtain a copolymer latex (A) of Synthesis Example 3.
[0103] Table 1 shows the average particle size of the latex particles in the copolymer latex (A).
[0104] 2. Production of copolymer latex (B)
[0105] In an autoclave equipped with a stirrer, water in the amount shown in Table 2, an emulsifier (specifically sodium dodecylbenzenesulfonate or sodium rosin acid), an electrolyte, and a polymerization initiator (specifically potassium persulfate) in the amount shown in Table 2 were added, and stirred.
[0106] Next, the monomer composition (b), chain transfer agent (specifically tert-dodecyl mercaptan), and hydrocarbon solvent (specifically cyclohexene) in the amounts shown in Table 2 were added, and polymerization was carried out while maintaining the internal temperature at the temperature shown in Table 2. The polymerization was terminated when the polymerization conversion rate reached 98%.
[0107] Next, an aqueous sodium hydroxide solution was added to adjust the pH to 8, and then unreacted monomers and the like were removed by steam distillation to obtain copolymer latexes (B) of Synthesis Examples 4 to 7 and Comparative Synthesis Examples 4 to 7.
[0108] Table 2 shows the average particle size of the latex particles in the copolymer latex (B).
[0109] [Table 2]
[0110] Table 2
[0111]
[0112] 3. Preparation of copolymer latex for adhesive
[0113] The copolymer latex (A) and the copolymer latex (B) were blended and mixed at the blending ratios shown in Tables 3 and 4 to obtain the adhesive copolymer latex of each Example and each Comparative Example.
[0114] [Table 3]
[0115] Table 3
[0116]
[0117] [Table 4]
[0118] Table 4
[0119]
[0120] 4. Preparation of Adhesive Composition
[0121] After adding 4 parts by mass of 10% sodium hydroxide to 260 parts by mass of water and stirring, 7.9 parts by mass of resorcinol and 8.6 parts by mass of 37% formalin were added, stirred and mixed, and aged at 30°C for 6 hours to synthesize a resorcinol-formalin resin. The solid content (evaporation residue) of the resorcinol-formalin resin was 4.1% by mass.
[0122] Next, water was added to 100 parts by mass of the adhesive copolymer latex of each example and each comparative example so that the solid content concentration of the adhesive composition became 16.5% by mass, and stirred. Then, the entire amount of the resorcinol-formalin resin (280.5 parts by mass) and 11.4 parts by mass of 28% ammonia water were added and stirred and mixed.
[0123] The ratio of the resorcinol-formalin resin in the adhesive composition was 11.5 parts by mass based on 100 parts by mass of the adhesive copolymer latex in terms of solid content.
[0124] Thereafter, 46.3 parts by mass of a 27% blocked isocyanate dispersion (SU-125F manufactured by Meisei Chemical Industry Co., Ltd.) was added, and the mixture was aged at 30° C. for 48 hours to obtain an adhesive composition.
[0125] 5. Evaluation
[0126] (1) Preparation of evaluation samples
[0127] Using a single-cord dip coater for testing, pretreated polyester tire cord (1500D / 2) was dipped in the adhesive composition of each Example and each Comparative Example, dried at 120°C for 120 seconds, and then sintered at 240°C for 60 seconds.
[0128] (2) Determination of the softness of tire cord
[0129] The polyester tire cord treated with the adhesive composition of each example and each comparative example was cut into pieces of 11 cm and measured with a hand dynamometer. The slit width of the hand dynamometer was set to 20 mm. The average value of 10 pieces was taken as the softness value.
[0130] The results are shown in Tables 3 and 4.
[0131] (3) Determination of adhesive strength
[0132] The polyester tire cord treated with the adhesive composition of each example and each comparative example was sandwiched between rubbers prepared with the following blending formula, and vulcanized and pressed at 160°C for 20 minutes (initial adhesion evaluation condition) or 170°C for 50 minutes (heat-resistant adhesion evaluation condition).
[0133] <Rubber formula>
[0134]
[0135] In addition, Anchigen RD is a 2,2,4-trimethyl-1,2-dihydroquinoline polymer.
[0136] The initial adhesion and heat-resistant adhesion between rubber and rubber reinforcing fibers were measured based on ASTM D2138-67 (H Pull Test).
[0137] The results are shown in Tables 3 and 4.
[0138] In addition, the above invention is provided as an exemplary embodiment of the present invention, but this is merely an example and is not to be construed as limiting. Modifications of the present invention that are obvious to a person skilled in the art are included in the scope of the claims described below.
[0139] Possibility of industrial application
[0140] The adhesive copolymer latex and adhesive composition of the present invention can be used to bond rubber and rubber reinforcing fibers.
Claims
1. A copolymer latex for an adhesive, characterized in that: Include: a copolymer latex A as an emulsion polymer of a monomer composition a containing 35 mass % to 75 mass % of a butadiene monomer, 10 mass % to 30 mass % of a vinyl pyridine monomer, and 10 mass % to 55 mass % of a styrene monomer; and a copolymer latex B of an emulsion polymer of a monomer composition b containing 3% by mass to 30% by mass of the butadiene monomer and 50% by mass to 85% by mass of the styrene monomer, The ratio of the solid content of the copolymer latex B to the total solid content of the copolymer latex A and the solid content of the copolymer latex B is 5% by mass or more and 15% by mass or less, The average particle size of the latex particles in the copolymer latex A based on the number of particles is less than 150 nm, and the average particle size of the latex particles in the copolymer latex B based on the number of particles is greater than 150 nm.
2. The adhesive copolymer latex according to claim 1, wherein The monomer composition b further contains 30% by mass or less of the vinyl pyridine monomer.
3. The copolymer latex for adhesive according to claim 1, characterized in that The monomer composition a contains 50% by mass or more of the butadiene monomer and 40% by mass or less of the styrene monomer.
4. The copolymer latex for adhesives according to any one of claims 1 to 3, wherein The ratio of the copolymer latex B to the total amount of the copolymer latex A and the copolymer latex B is 10% by mass or more.
5. An adhesive composition, characterized in that: Include: a copolymer latex A as an emulsion polymer of a monomer composition a containing 35 mass % to 75 mass % of a butadiene monomer, 10 mass % to 30 mass % of a vinyl pyridine monomer, and 10 mass % to 55 mass % of a styrene monomer; and a copolymer latex B of an emulsion polymer of a monomer composition b containing 3% by mass to 30% by mass of the butadiene monomer and 50% by mass to 85% by mass of the styrene monomer, and a resorcinol-formalin resin, The ratio of the solid content of the copolymer latex B to the total solid content of the copolymer latex A and the solid content of the copolymer latex B is 5% by mass or more and 15% by mass or less, The average particle size of the latex particles in the copolymer latex A based on the number of particles is less than 150 nm, and the average particle size of the latex particles in the copolymer latex B based on the number of particles is greater than 150 nm.
Citation Information
Patent Citations
Polyester fiber for reinforcing rubber and its production
JP1997021072A
Coating liquid for fiber coating and rubber reinforcing fiber using the same
JP2007314896A
Copolymer latex for adhesives
WO2011102003A1